Antiviral activity of povidone-iodine gargle and mouthwash solution against Enterovirus A71, Coxsackieviruses A16, A10 and A6 - W. X., Ang; S.H., Tan; K. T., Wong; David, Perera; Umah Rani, Kuppusamy; K.C., Ong (Malaysian Society of Parasitology and Tropical Medicine (MSPTM), 2024)
Hand, Foot and Mouth Disease (HFMD), a highly contagious viral disease common among infants and young children, is primarily caused by Enterovirus A71 (EV-A71) and Coxsackievirus A16 (CVA16). Nonetheless, emerging enteroviruses, such as CV-A10 and CV-A6, have also caused widespread outbreaks globally, in part due to the absence of effective antiviral therapies, and the high personto-person transmission rate. Persontoperson transmission is usually through fecaloral or oraloral routes, and sometimes via droplets. As the oral cavity is a primary site for early virus infection and replication, controlling oral viral shedding can mitigate the risk of transmission through this route. Povidone-iodine (PVP-I), a widely used antiseptic, has shown broad-spectrum antimicrobial properties but antiviral studies against HFMD-causing enteroviruses are limited, especially for CV-A10 and CVA6. Our study demonstrated that a 1% PVP-I solution (final concentration of 0.5%) exhibited virucidal activity against EV-A71, CV-A16, CV-A10, and CV-A6. All seven EV-A71 isolates and five CV-A16 isolates showed a significant virus titer reduction after a 1-minute incubation, while five CV-A10 isolates and two CV-A6 isolates required a 5-minute incubation to achieve this. The virucidal activity was confirmed through the EN14476:2013+A2:2019 virucidal quantitative suspension test, wherein all four viruses were completely inactivated after a 30-minute incubation with PVP-I at 37°C under both clean and dirty conditions. Western blot analysis suggested that PVP-I could affect the VP1 structural proteins of EV-A71. Our results suggest that PVP-I could serve as a potential virucidal agent to reduce the risk of person-to-person transmission of HFMD.